Development of an automated solid phase extraction instrument for determination of lead in high-salt foods. (15th March 2023) - Xiao, Yabing; He, Yihan; Ji, Chao; Hua, Marti Z.; Liu, Wei; Yang, Shuang; Chen, Da; Zheng, Wenjie; Lu, Xiaonan
Highlights: An instrument for solid phase extraction of heavy metals was developed. It consumes less reagent, saves time, and is easy to operate. The accuracy and stability were verified by inter-laboratory testing. Recovery was within 80.0%–100.0% and RSD was of 2.8%–9.3%. Abstract: In this study, an instrument for solid phase extraction of heavy metals was developed. Compared to conventional separation equipment, it has advantages of small size, less reagent consumption, time saving, easy operation, and good reproducibility. After analyzing the partition coefficient and adsorption capacity of the exchange resin, the Chelex-100 resin achieved a strong adsorption of lead at pH of 6.0. Compared to the matrix modifier method, solid phase extraction eliminated the interference of salts and the results were more accurate and reliable. The accuracy and stability of this instrument were verified by inter-laboratory testing of the quality control samples of soy sauce (CFAPA-QC1728-4), and the results from six laboratories were within the standard range with relative standard deviation (RSD) of 2.2%–2.8%. Recovery of three spiked samples was within 80.0%–100.0% and RSD was of 2.8%–9.3%, suggesting that this instrument can be used to separate and enrich lead in high-salt foods.